The impact of therapeutic group therapy on the life purpose of elderly people suffering from loneliness - Wijoyo, Eriyono Budi; Daulima, Novy Helena C.; Wardani, Ice Yulia; Rosyad, Habibi Rohman (Intelektual Pustaka Media Utama, 2023)
The elderly face a variety of psychological issues, including loneliness, as they reach the end of their human development stage. Some external stimuli are required to overcome loneliness because it affects the life goals of the elderly, which differ from those of younger people. Therapeutic group therapy (TGT) is one of the stimuli provided, and it trains the elderly to adapt to changes in their lives, including their life goals. A quasi-experimental study was used to evaluate the effect of therapeutic group therapy on the sense of purpose in life among lonely elderly people. Following the assessment of loneliness, 86 elderly people experiencing loneliness were recruited for this study and divided into two groups. The intervention group received health education on the development of the elderly as well as therapeutic group therapy. Only health education was provided to the control group. When compared to the control group, the elderly who experienced loneliness in the intervention group had a higher score on purpose of life.